How plants manage food reserves at night: quantitative models and open questions - Scialdone, Antonio; Howard, Martin (Frontiers in Plant Science, 2015)
In order to cope with night-time darkness, plants during the day allocate part of their photosynthate for storage, often as starch. This stored reserve is then degraded at night to sustain metabolism and growth. However, night-time starch degradation must be tightly controlled, as over-rapid turnover results in premature depletion of starch before dawn, leading to starvation. Recent experiments in Arabidopsis have shown that starch degradation proceeds at a constant rate during the night and is set such that starch reserves are exhausted almost precisely at dawn. Intriguingly, this pattern is robust with the degradation rate being adjusted to compensate for unexpected changes in the time of darkness onset. While a fundamental role for the circadian clock is well established, the underlying mechanisms controlling starch degradation remain poorly characterized. Here, we discuss recent quantitative models that have been proposed to explain how plants can compute the appropriate starch degradation rate, a process that requires an effective arithmetic division calculation. We review experimental confirmation of the models, and describe aspects that require further investigation. Overall, the process of night-time starch degradation necessitates a fundamental metabolic role for the circadian clock and, more generally, highlights how cells process information in order to optimally manage their resources.